2007
DOI: 10.1002/chin.200716243
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Steroids

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Almost all steroid molecules possess the same basic perhydroxyl cyclopentenophenanthrene skeleton. The differences in the basic skeleton and the attachment of different groups result in various classes of steroids [ 17 ]. Steroids have many pharmacological applications and the research is continuing to find out about these metabolites, as potential lead compounds in drug design and discovery [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Almost all steroid molecules possess the same basic perhydroxyl cyclopentenophenanthrene skeleton. The differences in the basic skeleton and the attachment of different groups result in various classes of steroids [ 17 ]. Steroids have many pharmacological applications and the research is continuing to find out about these metabolites, as potential lead compounds in drug design and discovery [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This showed that the whole Cassia ferruginea (Schrad D.C) root is rich in chemical constituents as investigated in this study. These principles have been known for many years to exhibit biological activity, such as effects on the central nervous system, and antibacterial, antiturmour, and anthehelmintic activity Thus, the presence of these phyto-constituents in the Cassia ferruginea (Schrad D.C) root bark and root core such as alkaloids which act as antiparasitic and treating gout [33]; tannins act against diarrhea [34]; steroid compounds as hormone stimulator and regulator [35]; and in the treatment of prostate cancer [36]; Saponins as anti-inflammatory, hypocholesterolemic and immune stimulating [37]; flavonoid prevent ulcer [38]; cardiac glycoside as potential anticancer [39]]; and phenolic compound possess anti-cancer ability [40] has indeed support the acclaimed wonders and their various uses traditionally. Thus, natural agent such as, water, the sun, air and Phytochemical constituents (medicinal herbs) which are gotten from healthy food, as well as the adoption of healthy habits (physical exercise, adequate rest, good mental health and trust in God) may do more for health than all powerful, chemically synthesized medicines or aggressive treatment.…”
Section: Fig-7: Phytochemical Screenings Results (Foam Test) Results mentioning
confidence: 99%
“…A steroid is a group of secondary metabolites derived from cholesterol; it has diverse chemical structure molecules possess the same basic perhydroxylcyclopentenophenathrene skeleton [16]. The differences in the basic skeleton and the attachment of different groups result in various classes of steroids [17]. Steroids have many pharmacological applications and research is continuing to find the other applications of the compound in drug design and discovery [18].…”
Section: Discussionmentioning
confidence: 99%